Current update on the visual outcome of optic pathway glioma associated with neurofibromatosis type-1 - Zeid, Janice Lasky (Frontiers in Surgery, 2022)
Purpose: The clinical and diagnostic evaluation in the follow-up of optic glioma patients with NF-1 can be difficult. Determining if and when to treat is a significant challenge in best managing these patients. Update on current information and future directions in management. Current Practice: NF-associated optic pathway gliomas present a significant management challenge with high stakes for visual outcomes. Monitoring vision and diagnostic tests are challenging in patients of a younger age. Regardless of if practices see few or many optic gliomas, a detailed discussion of the disease, screening, diagnostic tests, and treatment approach would be helpful in treating these patients. Summary: This review of optic gliomas -NF1 associated gliomas includes the current approach and knowledge of OPG-NF1 and future directions in OPG-NF1 management. This includes the ongoing Multicenter Natural History Study and other clinical trials and outcomes in NF-1 patients with Optic Pathway Gliomas.